Complementarity between Multilateral Lending and Private Flows to Developing Countries : Some Empirical Results - Ratha, Dilip (World Bank, Washington, DC, 2014)
Despite the surge in private capital flows in the 1990s, lending by the multilateral development banks continues to be a significant source of external finance for low-income and lower-middle-income countries. And for middle-income countries, which receive the lion's share of private flows, multilateral lending has played an important stabilizing role during times of credit rationing. Even though multilateral loans may have behaved countercyclically with respect to private flows in the short term, these loans also tended to complement private flows in the medium term by signaling-and often fostering-a better investment environment in the borrowing countries.